Interaksi sosial dalam Isun-isun Bajau. - Saidatul Nornis Hj. Mahali, (Universiti Kebangsaan Malaysia, 2008)
There are various folk genre belonging to the Bajau people. Among them is the Isun-Isun folk songs sung by the Kota Belud Bajaus. This is a popular folk song sung by the the Bajaus in Kota Belud. Hence this article will focus on the elements of social interaction found in these Isun-Isun.